Surface Investigation on Gd4M8 (M = Zn, Ni) Single Molecule Coolers. (5th May 2014) - Corradini, Valdis; Ghirri, Alberto; Candini, Andrea; Biagi, Roberto; del Pennino, Umberto; De Renzi, Valentina; Dotti, Gianluca; Otero, Edwige; Hooper, Thomas N.; Inglis, Ross; Brechin, Euan K.; Affronte, Marco
<x xml:space="preserve">Abstract</x> Proving the preservation of functionality at the molecular scale is still a major challenge, both for the choice of suitable derivatives and protocols and for the employed experimental tools and methods. By using a combined scanning probe (AFM and STM) and spectroscopic methodology (XPS, XAS and XMCD), it is shown that Gd4M8 derivatives (with M = Zn2+, Ni2+) are robust molecular units which preserve their electronic, magnetic, and thermodynamic properties when deposited on a metallic surface. Namely, entropy variation ΔS = [S(6 T) – S(0 T)] exceeding 8 R (20 J kg−1 K−1) at 4 K in isolated Gd4Ni8 molecules dispersed on Au(111) surface is measured and a viable route to exploit large magnetocaloric effect at single molecule level is shown.